Linguistic Reflections of Cultural Ethics: Social Assistance Discourse in Surakarta - Teisar Arkida; Fitri Anekawati; Wakit Abdullah Rais (Journal of Pragmatics Research, 2025)
This ethnolinguistic study explores the cultural, moral, and socio-political dimensions of social assistance discourse among citizens of Surakarta, Indonesia. Critical to addressing economic inequality, social assistance programs are examined through linguistic analysis of discourse digital ethnographically observed from January to March 2024, coinciding with increased political activity surrounding the presidential election. Data are drawn from social media discussions, which reveal the complex interaction between Javanese cultural values and contemporary socio-political realities in shaping perceptions of social assistance distribution. The results show that people in Surakarta view social assistance as a political ploy that exploits people's daily living conditions and ultimately violates moral values. The combination of Javanese and Indonesian terms reflects ethical considerations and community expectations of fairness and integrity in the distribution of social assistance. An analysis of cultural meanings identified three cultural interpretations: the politicization of social assistance, economic dependence in everyday life, and moral judgments embedded in the ethical framework of Javanese culture. Governments must adopt culturally sensitive policies that integrate local moral frameworks into aid distribution strategies, promoting transparency and accountability. By understanding the dynamics of these different languages and cultures, policymakers can design more compelling, ethically grounded social assistance initiatives that align with the values of the community in Surakarta and its surrounding areas.